Eine vergessene Konjektur J. G. Frazers zu Ov. Fast. 5, 74 - Ullrich, Heiko (Hyperboreus, 2025)
In Ov. Fast. 5, 74 the paradosis offers tangor, otherwise unattested as verbum dicendi governing an accusative with infinitive. Comparing Ov. Fast. 5, 625 f. and Verg. Aen. 7, 144, this note argues for reading rumor (proposed but then rejected by J. G. Frazer) instead of tangor explaining the corruption as a melting of a former gloss fama (perhaps corrupted into tam) into the original rumor producing the non-latin *famor or *tamor then emended by a scribe or corrector into the tangor of the manuscripts. Reconstructed rumor in 5, 74 allows for an interesting comparison between 5, 69–76 and 2, 491–508 showing how Ovid criticizes both the selfish senate of the late republic and the princeps who removed power from the republican institution in an arbitrary manner.